Penerjemahan Istilah Belanda dalam Bahasa Hukum Indonesia dan Dampaknya dalam Proses Peradilan - Dali, Meilina Widya; Rahma, Suchi Syafarina; Jamadi, M.; Purwasih, Siti Rati; Shintawati, Meilani Citra; Lahope, Elisabeth Agnes; Husain, Asraria; Limonu, Nurilla Arifachofsah; Tasiabe, Dwi Alex Chandra Dimuka; Tomu, Muhammad Fazrun; Hunowu, Akhdiat Daffa; Yacub, Mohammad Aditya; Alinti, Mohamad Satrio H.; Antu, Muhammad Kanz (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study examines the use of Dutch legal terms in the Indonesian legal system and their impact on judicial practice. The research is based on the continued application of colonial regulations that preserve Dutch terminology in the Criminal Code, Civil Code, procedural law, and court decisions. A qualitative approach was applied through document analysis of legislation, legal literature, and judicial rulings. The analysis focuses on identifying types of Dutch terms, translation patterns, and shifts in meaning. The findings reveal inconsistent translation practices that lead to divergent interpretations among legal practitioners. This situation affects the assessment of criminal elements, evidentiary processes, and public understanding of legal proceedings. The study highlights the need for standardization of legal language and the development of a national legal glossary to strengthen legal certainty and improve access to justice.